High-Intensity Interval Exercise May Improve Cardiac and Arterial Function in Systolic Heart Failure Patients - Rizzo, Toni (MD Conference Express, 2014)
This randomized study assessed the effects of an intense interval aerobic exercise program on cardiac and systemic arterial function in patients with congestive heart failure. Patients who adhered to the exercise program for 12-weeks experienced significant improvements in multiple aortic and diastolic parameters compared with patients with chronic heart failure who received usual care.